1996
DOI: 10.2307/2410787
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Morph-Specific Fitness Differences in Tristylous Lythrum salicaria

Abstract: In tristylous plant populations, style-morph frequencies are governed by an interaction between frequencydependent selection due to disassortative mating and stochastic processes. Provided that there are no inherent fitness differences among morphs, frequency-dependent selection should result in equal morph frequencies at equilibrium. Stochastic models indicate that the short-styled morph has the highest and the long-styled morph the lowest probability of being lost from local populations as a result of random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 33 publications
2
30
1
Order By: Relevance
“…From each population, 20 plants were randomly chosen that were 3 m apart to encourage genetic distinctiveness. Their seeds were considered to be half-sibs of the mother plant, given that purple loosestrife is an obligately outcrossing species (Å gren and Ericson 1996).…”
Section: Study Populations and Common Garden Experimentsmentioning
confidence: 99%
“…From each population, 20 plants were randomly chosen that were 3 m apart to encourage genetic distinctiveness. Their seeds were considered to be half-sibs of the mother plant, given that purple loosestrife is an obligately outcrossing species (Å gren and Ericson 1996).…”
Section: Study Populations and Common Garden Experimentsmentioning
confidence: 99%
“…Long-styled plants tend to produce fewer seeds and to be more strongly pollenlimited than mid-, and short-styled plants in several Swedish populations Å gren and Ericson, 1996;Waites and Å gren, 2004), whereas short-styled plants produce fewer seeds and are more strongly pollen limited in two North American populations (O'Neil, 1992). Long-styled plants tend to produce fewer seeds and to be more strongly pollenlimited than mid-, and short-styled plants in several Swedish populations Å gren and Ericson, 1996;Waites and Å gren, 2004), whereas short-styled plants produce fewer seeds and are more strongly pollen limited in two North American populations (O'Neil, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In Swedish populations of the tristylous, self-incompatible herb, Lythrum salicaria, the long-styled morph tends to produce fewer seeds per flower than the mid-and short-styled morphs because of differences in pollen limitation Å gren and Ericson, 1996;Waites and Å gren, 2004). Moreover, stigmas of the long-styled morph receive considerable amounts of incompatible pollen (Waites and Å gren, 2004).…”
mentioning
confidence: 99%
“…It has been suggested that such fitness intransitivity is the result of sexual selection and that it is the consequence of context-dependent female mate choice (Alonzo and Sinervo, 2001;Sinervo et al, 2007), but few evidence for this assumption exists. RPS games have been described in lizards (Sinervo and Lively, 1996;Sinervo et al, 2007), insects (Zhang et al, 2013), and bacteria (E. coli, Kerr et al, 2002), and it has been suggested by Sinervo and Calsbeek (2006), that they also exist in isopods (Shuster and Wade, 1991), other insects (damselflies, Svensson et al, 2005), and plants (Ågren and Ericson, 1996). In all these species (except in E. coli where direct competition may be the driving force; Kerr et al, 2002), sexual selection exerted by females might be at the origin of fitness intransitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, sexual selection may again explain the existence of fitness intransitivity, among genetic polymorphisms (Zhang et al, 2013). In the tristylous, self-incompatible herb Lythrum salicaria, three floral morphs (long-styled, mid-styled, short-styled) promote disassortative mating and they exhibit fitness intransitivity, the latter being governed by an interaction between negative FD selection among morphs and stochastic processes (Ågren and Ericson, 1996;Sinervo and Calsbeek, 2006). This suggests that sexual selection on morphs (genetic polymorphisms) is a crucial driver of most of the described RPS games, but thin evidence exists for its existence and importance, and for the critical role of female preference, which might accentuate the outcome of male-male competition (Alonzo and Sinervo, 2001).…”
Section: Introductionmentioning
confidence: 99%